1962
DOI: 10.1073/pnas.48.7.1222
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Deoxyribonucleic Acid in Ribonucleic Acid Synthesis, Iii. The Inhibition of the Enzymatic Synthesis of Ribonucleic Acid and Deoxyribonucleic Acid by Actinomycin D and Proflavin

Abstract: Actinomycin D is one of a number of polypeptide antibiotics isolated in Waksman's laboratory.1' 2 Bacteriostatic effects, particularly on gram positive bacteria, and antitumor activity have been attributed to this compound.2 3 Kirk4 has demonstrated that the addition of actinomycin D (0.2 to 0.5 ,4M) to exponentially growing cultures of Staphylococcus aureus stops RNA synthesis immediately. This effect is rapidly followed by an inhibition of protein synthesis, and later by a partial inhibition of DNA synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
86
0
1

Year Published

1963
1963
1977
1977

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 420 publications
(90 citation statements)
references
References 19 publications
2
86
0
1
Order By: Relevance
“…For this purpose, we have used actinomycin D, a highly specific inhibitor of R N A -D N A polymerase activity (6). Actinomycin effect is exerted on the template by complexing specifically and firmly with the primer DNA.…”
mentioning
confidence: 99%
“…For this purpose, we have used actinomycin D, a highly specific inhibitor of R N A -D N A polymerase activity (6). Actinomycin effect is exerted on the template by complexing specifically and firmly with the primer DNA.…”
mentioning
confidence: 99%
“…In vitro experiments have shown that acridines are intercalated between specific adjacent base pairs in DNA (Lerman, 1963) and inhibit synthesis of DNA (Hurwitz, Furth, Malamy &Alexander, 1962). The base specificity of the affinity has been demonstrated to differ according to the kinds of acridines (Tubbs, Eitmars & van Winkle, 1964;Weisblum & de Haseth, 1972).…”
Section: Eflect Of Fatty Acids On Curingmentioning
confidence: 99%
“…RNA x synthesis in isolated thymus nuclei was found to be DNA dependent (Allfrey and Mirsky, 1962) and a similar dependence may apply to all cellular RNA synthesis (Hurwitz et al, 1962; also for references). The restriction of DNA to the chromosomes gives chRNA a unique position since it should contain RNA newly synthesized under the influence of DNA.…”
mentioning
confidence: 91%